Upregulated PCAT-1 predicts poor prognosis and reduced immune cell infiltration in head and neck squamous cell carcinoma through the miR-145-5p / FSCN-1 axis - Pirhoushiaran, Maryam; Heidarzadehpilehrood, Roozbeh; Mokhtarinejad, Mahnoosh; Hesami, Sara; Rezaei, Nima; Farahani, Abbas Shakoori (Springer Science and Business Media B.V., 2025)
Background: LncRNA PCAT-1 is known to promote cancer proliferation, invasion, and metastasis. However, its significance in HNSCC is not fully understood. This research investigates how the PCAT-1 / miR-145-5p / FSCN-1 axis promote HNSCC. Methods and Results: We analyzed the gene expression patterns on 238 fresh-frozen samples, comparing tumors with their normal adjacent tissues (NATs). HNSCC samples showed higher PCAT-1 and FSCN-1 expression compared to NATs (p < 0.001 and p < 0.001, respectively). In contrast, miR-145-5p expression was markedly downregulated compared to NATs (p < 0.001). Notably, ROC curve analysis revealed exceptional diagnostic power, with an AUC of 0.83 for PCAT-1, 0.95 for miR-145-5p, and 0.91 for FSCN-1. Pearson correlation analysis unveiled a significant positive correlation between PCAT-1 and FSCN-1 expression levels (r = 0.084, p < 0.001) and negative correlations between FSCN-1 and miR-145-5p (r = -0.710, p < 0.001) as well as between PCAT-1 and miR-145-5p (r = -0.759, p < 0.001). Distinct molecular profiles were observed in the levels of PCAT-1, miR-145-5p, and FSCN-1 between HPV (-) and HPV (+) 16 and 18 genotypes (p = 0.007, p = 0.027, and p = 0.002). MiR-145-5p expression showed significant differences between HPV (-) and HPV (+) other genotypes (p = 0.035). FSCN-1 expression showed notable distinctions between HPV (+) 18 & 16 and HPV (+) other genotypes (p = 0.031). Conclusions: Elevated levels of lncRNA PCAT-1 promote HNSCC through the miR-145-5p/FSCN-1 axis and are associated with poor prognosis and reduced immune cell infiltration levels.